Depresi Silangdalam Kelapa Dalam Mapanget Berdasarkan Penanda Mikrosatelit (SSR) - DONATA S. PANDIN (Buletin Palma, 2009)
Inbreeding Depression Analysis Based on Microsatellite (SSRs)Markers in Mapanget Tall CoconutThe objective of this research was to determine inbreeding depression based on microsatellite (SSR) markers of second, third, and fourth generations of selfed Mapanget Tall coconut No.32 (DMT-32). The research was conducted in Plant Biology Laboratory, Research Center of Plant Genetic Resources and Biotechnology, Institut Pertanian Bogor. The research was done since May 2004 until May 2007. Fifteen out of 19 microsatellite ( , SSR) loci (primers) were used to analyze inbreeding depression in each generation of selfed Mapanget Tall coconut No.32. Based on 15 loci of microsatellite (SSRs) markers, showed that inbreeding depression expressed and have tendency to increase from generation to next generation of selfed Mapanget Tall coconut No.32 (DMT-32). Inbreeding depression in DMT-32 S2 (2.78%), DMT-32 S3 (10.54%), and DMT-32 S4 (15.74%). Four out of 15 microsatellite loci used were not in Hardy-Weinberg equilibrium, means that in DMT-32 S4 those loci were homozygote that’s why alleles of those loci were not inherits in equilibrium. DMT-32 S4 coconut can be used as plant materials to find progeny with higher heterosis level.